2010
DOI: 10.1007/s00204-010-0520-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in hepatic expression and activity of cytochrome P450 in male rats

Abstract: Age-related changes in hepatic expression and activity of cytochrome P450 (CYP) were investigated in male rats aged 3 (weanling), 12 (young), 26 (adult), and 104 (old) weeks. Levels of microsomal protein, total CYP, and cytochrome b(5) increased fully after puberty. CYP1A1 was detected only in 3-week-old rats, and CYP1A2, CYP2B1, and CYP2E1 were maximally expressed at 3 weeks but decreased at 12 and 26 weeks. CYP2C11 and CYP3A2 increased markedly after puberty and decreased with aging. Ethoxyresorufin-O-deethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
47
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 27 publications
12
47
3
Order By: Relevance
“…CYP2B expression changes through development; early adolescent rats had higher levels of hepatic CYP2B protein compared with adults (Yun et al, 2010). However, our data do not support a faster conversion of nicotine to cotinine in the early adolescent cohort, as both nicotine and cotinine levels are lower.…”
Section: Discussioncontrasting
confidence: 81%
“…CYP2B expression changes through development; early adolescent rats had higher levels of hepatic CYP2B protein compared with adults (Yun et al, 2010). However, our data do not support a faster conversion of nicotine to cotinine in the early adolescent cohort, as both nicotine and cotinine levels are lower.…”
Section: Discussioncontrasting
confidence: 81%
“…37 These changes may be the result of increased blood flow throughout the body or increased expression of some CYPs in the liver, as observed for CYP2Cs, CYP2Bs, and CYP1A proteins in our study. Moreover, although CYP1A2 protein levels have been shown to decrease with aging, 38 we found that CYP1A protein levels were increased in the swimming exercise group compared with the control group.…”
Section: Discussioncontrasting
confidence: 64%
“…38 For example, CYP1A2, CYP2B1, and CYP2E1 levels were increased in 3-week-old rats compared with those in 12-, 26-, and 104 week-old rats. Moreover, CYP2C11 and CYP3A2 expression has been shown to decrease with age.…”
Section: Discussionmentioning
confidence: 88%
“…Some variations within groups regarding uptake of radioactivity in the liver (Fig. 3C) might be explained by age-related differences in biodistribution related to changes in enzyme activity and isoform distributions during aging, as reported in several studies (28)(29)(30).…”
Section: Discussionsupporting
confidence: 55%